Integrating Islamic and Pancasila Education in the Character Development of 12th Grade Students at Karya Dharma Veteran High School, Sambi Subdistrict, Boyolali Regency, Academic Year 2023/2024 - Slamet, Rochmat; Sugiyat, S; Sukari, S (Yayasan Rahmat Islamiyah, 2025)
This study aims to find out how the implementation of the integration of Islamic Education and Pancasila moral education in Grade 3 students of Senior High School by veteran dharma Sambi Boyolali, how the role of the integration of Islamic Education and Pancasila moral education on the formation of character of Grade 3 students of Senior High School by veteran dharma Sambi Boyolali and how the perception of teachers, students and guardians of Grade 3 students of Senior High School by veteran dharma Sambi Boyolali towards the implementation of educational integration Islam and Pancasila moral education in learning. This study uses a qualitative method with a descriptive approach. Data collection was carried out by interview, observation, and documentation methods. To test the validity of the data, it was carried out using source triangulation and triangulation techniques. As for the data analysis technique, it uses data reduction, data presentation, and conclusion. The results of the study can be concluded that the integration of Islamic Education and Pancasila Moral Education in Grade 3 of SMA Karya Dharma Veteran Sambi Boyolali received a positive response from teachers, students, and guardians. Despite the challenges in their implementation, stakeholders are aware of the importance of these values in shaping students' character and their social lives. The involvement and support of all parties is essential to achieve the success of this program.